Use of HbA1c in the identification of patients with hyperglycaemia caused by a glucokinase mutation: observational case control studies. - Anna M Steele; Kirsty J Wensley; Sian Ellard; Rinki Murphy; Maggie Shepherd; Kevin Colclough; Andrew T Hattersley; Beverley M Shields (PLoS ONE)
Aims HaemoglobinA1c (HbA1c) is recommended for diabetes diagnosis but fasting plasma glucose (FPG) has been useful for identifying patients with glucokinase (GCK) mutations which cause lifelong persistent fasting hyperglycaemia. We aimed to derive age-related HbA1c reference ranges for these patients to determine how well HbA1c can discriminate patients with a GCK mutation from unaffected family members and young-onset type 1 (T1D) and type 2 diabetes (T2D) and to investigate the proportion of GCK mutation carriers diagnosed with diabetes using HbA1c and/or FPG diagnostic criteria. Methods Individuals with inactivating GCK mutations (n = 129), familial controls (n = 100), T1D (n = 278) and T2D (n = 319) aged ≥18years were recruited. Receiver Operating Characteristic (ROC) analysis determined effectiveness of HbA1c and FPG to discriminate between groups. Results HbA1c reference ranges in subjects with GCK mutations were: 38-56 mmol/mol (5.6-7.3%) if aged ≤40years; 41-60 mmol/mol (5.9-7.6%) if >40years. All patients (123/123) with a GCK mutation were above the lower limit of the HbA1c age-appropriate reference ranges. 69% (31/99) of controls were below these lower limits. HbA1c was also effective in discriminating those with a GCK mutation from those with T1D/T2D. Using the upper limit of the age-appropriate reference ranges to discriminate those with a mutation from those with T1D/T2D correctly identified 97% of subjects with a mutation. The majority (438/597 (73%)) with other types of young-onset diabetes had an HbA1c above the upper limit of the age-appropriate GCK reference range. HbA1c ≥48 mmol/mol classified more people with GCK mutations as having diabetes than FPG ≥7 mmol/l (68% vs. 48%, p = 0.0009). Conclusions Current HbA1c diagnostic criteria increase diabetes diagnosis in patients with a GCK mutation. We have derived age-related HbA1c reference ranges that can be used for discriminating hyperglycaemia likely to be caused by a GCK mutation and aid identification of probands and family members for genetic testing.